2012
DOI: 10.1111/j.1529-8817.2012.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

DINOPHYSIS CAUDATA (DINOPHYCEAE) SEQUESTERS AND RETAINS PLASTIDS FROM THE MIXOTROPHIC CILIATE PREY MESODINIUM RUBRUM1

Abstract: "Phototrophic"Dinophysis Ehrenberg species are well known to have chloroplasts of a cryptophyte origin, more specifically of the cryptophyte genus complex Teleaulax/Geminigera. Nonetheless, whether chloroplasts of "phototrophic"Dinophysis are permanent plastids or periodically derived kleptoplastids (stolen chloroplasts) has not been confirmed. Indeed, molecular sequence data and ultrastructural data lead to contradictory interpretations about the status of Dinophysis plastids. Here, we used established cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 31 publications
3
50
0
1
Order By: Relevance
“…In the case of Dinophysis caudata, kleptochloroplasts make their way into the dinoflagellate cytoplasm via the food vacuoles, and then elongate toward the periphery of the cell. At the same time, the kleptochloroplasts are highly modified not only with regard to their shape but also with regard to the arrangement of the thylakoids relative to the pyrenoid (Kim et al 2012). As in H. arenicola and D. caudata, the kleptochloroplast of Amphidinium poecilochroum and Gymnodinium aeruginosum also become highly modified under experimental conditions.…”
Section: Enlargement Of the Kleptochloroplastmentioning
confidence: 72%
See 4 more Smart Citations
“…In the case of Dinophysis caudata, kleptochloroplasts make their way into the dinoflagellate cytoplasm via the food vacuoles, and then elongate toward the periphery of the cell. At the same time, the kleptochloroplasts are highly modified not only with regard to their shape but also with regard to the arrangement of the thylakoids relative to the pyrenoid (Kim et al 2012). As in H. arenicola and D. caudata, the kleptochloroplast of Amphidinium poecilochroum and Gymnodinium aeruginosum also become highly modified under experimental conditions.…”
Section: Enlargement Of the Kleptochloroplastmentioning
confidence: 72%
“…The kleptochloroplasts lie directly in the dinoflagellate cytoplasm, and not in the food vacuole . Recently, the process of kleptochloroplast isolation in D. caudata was revealed ultrastructurally (Kim et al 2012). The study showed that D. caudata takes up kleptochloroplasts together with other organelles of M. rubrum into a food vacuole, and then isolated the kleptochloroplasts from the food vacuole into the dinoflagellate cytoplasm (Kim et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations